Dinamika Interaksi Kelas dalam Flipped Classroom: Studi Kasus pada Mata Kuliah Strategi Belajar Mengajar SD: Dynamics of Class Interaction in Flipped Classroom: A Case Study on Elementary School Teaching and Learning Strategy Course - Sianturi, Canni Loren; Tambunan , Janwar; Tamba , Vivi Alexia (ITScience (Information Technology and Science), 2024)
This study examines in depth the dynamics of classroom interactions in the Flipped Classroom learning model in the Elementary School Teaching and Learning Strategy course at the Elementary School Teacher Education Study Program, HKBP Nommensen University, Pematangsiantar during the even semester of the 2023/2024 academic year. With a qualitative approach and case study design, data were collected through observation, interviews, and documentation studies. The results showed that providing pre-class materials significantly improved students' readiness and understanding before class discussions. Class discussions became more in-depth and interactive thanks to this preparation, while the use of learning videos made it easier to understand complex concepts. Formative assessments provided immediate and useful feedback for students to improve their weaknesses, while focusing on metacognitive skills such as reflection and planning helped in the development of more effective learning strategies. Flipped Classroom has also been shown to improve students' time management and productivity, as well as enrich social interactions in the classroom through active involvement in both in-class and out-of-class discussions. This model is flexible in assignments, which significantly increases student motivation and engagement. In conclusion, Flipped Classroom not only improves academic understanding but also plays an important role in developing students' social and metacognitive skills, making it an effective learning model in the era of the industrial revolution 4.0.